Application of the Learning Model to Achieve Increased Awareness of Students Regarding the Proclamation of Indonesian Independence - Aulia Nisa Asyani; Siti Fatimah; Tuti Istiani; Muh. Husen Arifin (Institut Pendidikan Indonesia, 2021)
This research is motivated by the development of human resources through social sciences which must be introduced to students at an early age. Of course, in introducing social sciences, teachers must use learning models so that teaching and learning activities can be achieved in accordance with learning objectives. The formulation of the problem in this research article is how a teacher conveys learning related to social sciences. Apart from that, what learning models can teachers use in teaching social sciences? The aim of this research is so that readers can understand the many learning models that can be used to increase students' understanding of the Proclamation of Indonesian Independence. This research uses a qualitative research method which uses types of data in the form of results from journal literature, books and other scientific papers as references for writing research. The results of this research show that there are several learning models that educators can use in teaching and learning activities about the Proclamation of Indonesian Independence.